Aktivitas Antioksidan dan Kualitas Es Krim Tradisional Labu Kuning (Cucurbita muschata) dengan Penambahan Ekstrak Kulit Buah Naga Merah Sebagai Pewarna Alami - Saparingga, Latifah Eri (2016)
Pumpkin ice cream is a frozen food product which is the raw material of yellow squash has a sweet taste, soft texture, and is able to provide sensani cold. Pumpkin ice cream contains antioxidants, carbohydrates, protein, fat, vitamin A, vitamin, water, vitamin C ped red dragon fruit extract can lower cholesterol in the blood, so it can be used as a natural dye ice cream. The research objective was to determine the effect of the pumpkin with a red dragon fruit peel extract on organoleptic quality and antioxidant activity in the traditional ice cream. The method used in the study is completely randomized design (CRD) two factors, the first factor that pumpkin 6 g (L1), 7 g (L2), 8 g (L3) and the second factor bark extract red dragon fruit 4 g (N1), 6 g (N2), 8 g (N3). Descriptive data analysis using quantitative and qualitative. Research results show that the presence of the real effect of the addition of pumpkin with ped extracts red dragon fruit to the organoleptic quality (texture, color, aroma, flavor, and acceptance) in the treatment of pumpkin 8 g with skin extracts red dragon fruit 6 g (L3N2) has orange color, sweet taste, aroma fairly typical pumpkin, soft texture and acceptance of love and the highest levels of antioxidant activity by 35.90% in the treatment of pumpkin 6 g with dragon fruit peel extract 8 g (L1N3). Keywords : antioxidants, red dragon fruit peel, pumpkin ice cream.